Wei Chang An pill regulates gastrointestinal motility in a bidirectional manner. (1st January 2021) - Jia, Sitong; Chai, Lijuan; Zhang, Jing; Zhang, Min; Li, Lin; Qi, Yaxin; Pang, Yafen; Chen, Xi; Fan, Nana; Wang, Lin; Wang, Yujing; Song, Jixiang; et al.
Abstract: Context: Wei Chang An (WCA) is a commercial prescription developed for the coordination of gastrointestinal movement. Objective: To investigate the role of WCA in the regulation of diarrhoea and constipation in rats. Material and methods: The diarrhoea and constipation models were prepared by gavage of Folium senna and diphenoxylate hydrochloride. Rats were randomized equally ( n  = 6) into the normal group given saline daily, the positive group given Pinaverium Bromide (13.5 mg/kg) or Sennoside A (0.1 mg/kg) and three WCA-treated groups (22, 44, and 88 mg/kg) by gavage daily for 7 consecutive days. The effects of WCA were assessed by a series of faecal symptoms and histopathology. Gastrointestinal parameters were determined by ELISA. The effect of WCA on gastrointestinal tissues was evaluated by strip assay. Expression of ROCK-1 and MLCK was measured by RT-PCR and Western blotting. Results: Data from Bristol stool form scale, diarrhoea index, visceral sensitivity, defaecation time, and intestinal propulsive rate showed that WCA protected rats against diarrhoea and constipation ( p  < 0.01). The up-regulation of Substance P and 5-hydroxytryptamine in diarrhoea rats and down-regulation of Substance P and vasoactive intestinal polypeptide in constipation rats were inhibited by WCA ( p  < 0.05). WCA stimulated the gastrointestinal strip contractions but inhibited ACh-induced contractions ( p  < 0.01). The decreased ROCK-1 and MLCK expression in diarrhoea rats and increased in constipation rats were suppressed by WCA ( p  < 0.01). Conclusions: WCA has both antidiarrhea and anti-constipation effects, suggesting its bidirectional role in gastrointestinal modulation, and providing evidence of WCA for irritable bowel syndrome treatment.